The Influence of Malay Architecture Style on The Elements of Facade in Palembang Limas House - Irma Indriani; Aditha Maharani Ratna; Andy Budiarto (Tesa Arsitektur, 2019)
The spreading of Malayans to South East Asia affected the development of architecture identity in Indonesia. This phenomenon appeared through the trace of Malay architectural traits on the façade of the old traditional houses in Palembang. This research was carried out using qualitative descriptive method by investigating how influencing rules of Malay architecture absorbed and visible on elements of the facades of the traditional houses of Palembang. The aim of the study is to obtain the how Malay architecture has influenced elements of facades of Palembang limas houses architecture. The findings showed that the architecture of Palembang limas houses has been adapting the style of Malay architecture to particular elements, which are roof, walls, ornaments, and stairs. Some differences between them might be possible due to the influence of local culture and natural environment.